Development of Smart Waste Bin with Segregation System Protoype - farhan, Amirulfarhanfauzilan; AMERUDDIN, AMIRA SARYATI (Enhanced Knowledge in Sciences and Technology, 2024)
In the current era of rapid global development, the substantial generation of electronic, plastic, and biodegradable waste poses a critical environmental challenge, especially in developing nations where waste management is often neglected. Ineffective waste disposal can lead to pollution, health risks, and resource waste. Therefore, the smart waste bin with segregation system prototype connected with Iot dashboard is built to overcome the problems. This work utilizes an Arduino UNO R3 microcontroller, inductive proximity sensors for metal detection, a moisture sensor for gauging waste moisture, and ultrasonic sensors for measuring waste levels together with Servomotors also are enabled to precise the sorting control for the waste collection. The system is integrated with Node-RED user-friendly interface for realtime monitoring. The seamless coordination between the sensor’s detection and precise servomotor control ensures accurate sorting of each waste category into designated compartments for further processing or disposal. This automation system improves waste sorting effectiveness and boosts the overall efficiency of waste management systems, promoting recycling initiatives and encouraging environmentally responsible practices for wet waste, metal waste, and other waste categories. The system’s potential usage in public spaces offers a solution to optimize waste management and contribute to a cleaner and more environmentally conscious public infrastructure. furthermore, .system’s usability can be enhanced to provide a platform for effective data management and analysis related to waste management.